Business Strategy Evaluation At PT. Pelabuhan Indonesia (Persero) Regional 4 Makassar - Andi Muh Jisr Bustami; Mahlia Muis (STIE Amkop Makassar, 2023)
This study aims to identify internal and external factors as evaluation material to provide an overview and position of the company and selection of the best stragic alternatives.This research is descriptive and conducted by qualitative and quantitative data input that contained in the IFE Matrix, EFE matrix and QSPM. Samples and data collection were carried out by distributing 24 questionaires aimed for company’s mid-level and top-level management. The results of this study indicate that at the input stage, the results of IFE matrix show an accumulated total score of 2,48, while in EFE matrix show an accumulated total score of 2,68. At the matching stage, the results shown in the IE matrix are the company’s position is in the V quadran, which is hold and maintain. Whereas in the SWOT diagram the company’s position is in the I quadran which support an aggressive strategy. At the decision stage, based on accumulation of TAS in the QSPM, the highest score from 8 alternative strategic choice is “Development of business and company’s management through strategic partnership with other subholding